IMPLIKASI BIG DATA ANALYTICS DALAM BIDANG AUDIT: A SYSTEMATIC LITERATURE REVIEW - Aulia Dwi Paresti; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
This research uses a qualitative method with a systematic literature review approach to get a clear and comprehensive picture of the implications of big data analytics in auditing. The research was conducted by collecting, analyzing, and synthesizing articles relevant to the research topic from 2019 to 2024 from various digital libraries such as Scopus, Emerald, Researchgate, Taylor & Francis Online, and ScienceDirect. The results show that the use of big data analytics can improve the efficiency of the audit process and audit quality. However, its use still faces challenges such as limited resources, lack of official guidance from regulators, and environmental challenges, especially in developing countries. This study is expected to enrich the literature related to the implications of big data analytics in the audit field, as well as provide practical benefits for audit firms that are considering using this technology to improve audit quality.